Hubungan antara Dukungan Keluarga, Faktor Psikologis, Status Ekonomi dan Pengetahuan Tentang Perawatan Bayi dengan Kesuksesan Pemberian Air Susu Ibu Eksklusif di area Puskesmas I Denpasar Timur - I Gusti Ngurah Suryantha; Angel Lim; Putu Indah Budiapsari (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Abstract Exclusive breastfeeding is important to reduce infant mortality and morbidity which is still high in Indonesia. The coverage of exclusive breastfeeding in Bali Province has reached the target of the Ministry of Health's 2019 Strategic Plan, which is 59.7%. However, several regencies/cities, one of which is Denpasar (47.6%), still have not reached the Strategic Plan target of 50%. The purpose of this study was to determine the relationship between family support, psychological factors, economic status and knowledge about infant care with the success of exclusive breastfeeding in the Work Area of ​​Puskesmas I, East Denpasar. The design of this study was analytic with a cross-sectional approach. Population namely; There are 120 mothers who have babies aged 6-12 months in the working area of ​​Puskesmas I Denpasar Timur. Respondents were selected by purposive sampling as many as 65 people. The variables in this study were family support, psychological state, economic status, infant care, and mother's success in exclusive breastfeeding. Data were collected using a questionnaire and have been tested for validity and reliability. Univariate data analysis to determine the percentage of occurrence of each variable studied and bivariate analysis using the chi-square test with a significance degree of sig (p <0.05). The results of this study indicate that family support affects the success of exclusive breastfeeding, where p value = 0.000 <0.05, psychological factors affect the success of exclusive breastfeeding where p value = 0.000 <0.05, economic status does not affect the success of exclusive breastfeeding where p value = 0.692> 0.05, and knowledge about infant care affects the success of exclusive breastfeeding p value = 0.000 <0.05.